Global tendencies in turkey meat production, trade and consumption - Kálmán, Ákos; Szőllősi, László (Acta Agraria Debreceniensis, 2023)
Global meat production totaled 357 million metric tons in 2021. Poultry accounted for nearly 40 percent of total meat production, including 4.2 percent of turkey meat (5.8 million tons). Global turkey meat production has stagnated between 5.5 and 6.0 million tons since 2008, in contrast to the monotonous upward trend in poultry meat production. Turkey meat production generally occurs under well-integrated conditions, with some large multinational companies and smaller, regional players. The industry is exposed to a number of factors that affect supply and demand, including disease outbreaks, government regulations, consumer preferences, and economic conditions. Key factors driving market growth include population growth, urbanisation, and increasing consumer awareness of the health benefits of turkey meat over other meats. In addition, advances in processing, packaging, and distribution technology have improved turkey meat's shelf life and availability, further fueling growth. Turkey farming and production are mainly concentrated in certain regions such as North America and Europe, where industrialisation has a long history and infrastructure is well developed. Turkey meat production in these areas is sufficient to meet local demand and is often exported to other regions. However, in other regions where turkey farming is less developed, such as parts of Asia and Africa, turkey meat production is insufficient to meet local demand. This type of meat must be imported from other regions. The degree of self-sufficiency in turkey meat depends on the level of development of the sector in each region. This study investigates the factors affecting global and regional markets for turkey meat and systematised the development of global consumption, production, and trade of turkey meat.